2019
DOI: 10.3389/fvets.2019.00193
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Community-Based Dog Welfare and Rabies Project in Sanur, a Sub-district of the Indonesian Island Province of Bali

Abstract: The Indonesian island province of Bali experienced its first rabies incursion in 2008. Mass vaccination of the dog population has proven effective and rabies cases in dogs and people have decreased, however the virus is still circulating among the dog population. Vaccination coverage must be maintained until rabies elimination. Increasing efficiency and effectiveness of vaccination campaigns is therefore desired. Community engagement leading to preventative health actions by community members can reduce diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 20 publications
2
20
1
3
Order By: Relevance
“…Sometimes behaviours were only broadly defined in the methodology, but able to be deduced from the evaluation measurements used. For example, Utami et al [ 47 ] aimed for owners to ‘provide better care [for] their dogs’ (p. 2), and for dogs to be presented for vaccination (p. 3). Evaluation measures included self-reported confinement practices and animal outcomes such as body condition scores, skin problems, and sterilisation status.…”
Section: Discussion Of Design and Evaluation Elementsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sometimes behaviours were only broadly defined in the methodology, but able to be deduced from the evaluation measurements used. For example, Utami et al [ 47 ] aimed for owners to ‘provide better care [for] their dogs’ (p. 2), and for dogs to be presented for vaccination (p. 3). Evaluation measures included self-reported confinement practices and animal outcomes such as body condition scores, skin problems, and sterilisation status.…”
Section: Discussion Of Design and Evaluation Elementsmentioning
confidence: 99%
“…Two studies utilised the Theory of Change approach [ 47 , 66 ] which is characterised by first defining a long-term goal before mapping backwards the steps required to reach that goal. The application of this theory by Utami et al [ 47 ] demonstrated the proposed relationships between target owner behaviours (‘guardians take good care of dogs’ and ‘dogs are presented for vaccination’ p. 3) and their ultimate goal (rabies control), but did not incorporate antecedents of the target behaviours. Therefore, they did not articulate the mechanism of change, i.e., how the intervention would change behaviour.…”
Section: Discussion Of Design and Evaluation Elementsmentioning
confidence: 99%
See 3 more Smart Citations